Kepemimpinan Transformasional dalam Lembaga Paud untuk Menyongsong Pendidikan Abad 21 - Dina Safira; Nayla Shafa Az-Zahra; Zahirah Nur Rahmah; Marsa Alifia; Celia Cinantya; Aslamiah Aslamiah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Early childhood education plays an important role in the formation of children's personality and development. This study aims to identify the application of transformational leadership in Early Childhood Education institutions to welcome 21st century education. The important key in creating an innovative, adaptive and creative learning environment lies in the transformational leadership style so as to increase children's potential to the fullest. The method used in this research is a literature review, by analyzing various relevant literature sources to assess the impact and importance of transformational leadership in the world of early childhood education. Transformational leadership has enormous potential, so the results of this study can help realize a generation that is not only intellectually intelligent, but also socially and emotionally developed, in accordance with the demands of an ever-evolving world.